2010
DOI: 10.1002/prot.22794
|View full text |Cite
|
Sign up to set email alerts
|

Fold versus sequence effects on the driving force for protein‐mediated electron transfer

Abstract: Electron transport chains composed of electron transfer reactions mainly between proteins provide fast, efficient flow of energy in a variety of metabolic pathways. Reduction potentials are essential characteristics of the proteins because they determine the driving forces for the electron transfers. Since both polar and charged groups from the backbone and side chains define the electrostatic environment, both the fold and the sequence will contribute. However, while the role of a specific sequence may be det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 69 publications
5
31
0
Order By: Relevance
“…This 'DFT þ PB' approach may be considered a zeroth-order solution that ignores the interactions between the inner and outer spheres other than the classical interactions between the partial charges of the outer sphere and the inner sphere in the two oxidation states. Although this approach may seem crude, our DFT þ PB calculations of reduction potentials are in excellent agreement with electrochemical measurements [29]. Moreover, deviations from the zeroth-order solution allow us to identify unique interactions not accounted for in the simple picture.…”
Section: S Niu and T Ichiye 574supporting
confidence: 72%
See 3 more Smart Citations
“…This 'DFT þ PB' approach may be considered a zeroth-order solution that ignores the interactions between the inner and outer spheres other than the classical interactions between the partial charges of the outer sphere and the inner sphere in the two oxidation states. Although this approach may seem crude, our DFT þ PB calculations of reduction potentials are in excellent agreement with electrochemical measurements [29]. Moreover, deviations from the zeroth-order solution allow us to identify unique interactions not accounted for in the simple picture.…”
Section: S Niu and T Ichiye 574supporting
confidence: 72%
“…On the other hand, our calculations also showed that when the thiolate ligands have dihedral angles corresponding to Fd, localisation of the minority spin is induced on one layer (Figure 13), leading to a large decrease in %L with only small changes in the redox energy when the thiolate ligands have dihedral angles corresponding to HiPIP, which has the typical delocalised minority spin for both redox layers. These findings suggest that the conformations of the cysteinyl ligands give rise to large changes in %L between the Fds and the HiPIPs but only contribute ,100 mV to the differences in reduction potential between the two, consistent with the large contributions from the surrounding protein calculated by DFT þ PB [29].…”
Section: Examining Ligand Tuning Of the Inner Spheresupporting
confidence: 71%
See 2 more Smart Citations
“…The clusters of both BSSβ and BSSγ do appear to play a structural role in that their removal leads to dissociation of the subunits from BSSα (16), which in turn leaves BSSα prone to unfolding and clearance by cellular degradation machinery in vivo (16) and sensitive to proteases in vitro. In terms of whether these clusters also play a redox role in addition to the above structural role, we find that the overall fold of both subunits is derived from a HiPIP, a family of [4Fe-4S] cluster proteins known for their high redox potentials (100-450 mV) and for their ability to stabilize clusters in the +3 oxidation state (20,27). A universal pattern of hydrophobic shielding of the [4Fe-4S] clusters in HiPIPs is believed to be responsible for shifting the +3/+2 redox potential into a biologically relevant range and shifting the +2/+1 couple out of a biological window, with potentials of -1.75 V (28).…”
Section: Discussionmentioning
confidence: 99%